Multidisciplinary team approach to headache care. (March 2012) - Jensen, Rigmor Højland; Rasmussen, Annette
SUMMARY Most patients with chronic headache are severely affected and characterized as refractory to treatment. The individual and societal burden of chronic headache is very high. Pharmacological treatment may be insufficient and is often associated with side effects so other aspects of pain management are often required. In recent years, international guidelines for multidisciplinary treatment of headache have been introduced and many headache centers have successfully included these elements in their treatment strategies. Evidence for the effect of such integrated headache care is now accumulating and a review of the existing literature is presented here.